2018
DOI: 10.1039/c8ra04537b
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic and electronic properties of CrO2 at multimegabar pressures

Abstract: CrO2 can undergo the pressure-induced phase transition sequence of rutile-type → CaCl2-type → pyrite-type → Pnma → (Fe2P-type→) I4/mmm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 59 publications
(106 reference statements)
3
18
0
Order By: Relevance
“…Regarding the thermodynamics of adsorption on the surface, we have calculated an adsorption energy of 0.7 eV. The Sn–O bond length is found to be 2.31 Å, which is close to the experimental Sn–O bond length in SnO 2 (~2.1 Å 70 ). We also found that the O–O distance is stretched by over 0.1 Å beyond the bond length of the O 2 molecule; this elongation suggests that the O 2 molecule is likely to be dissociated on the surface and may subsequently participate in the formation of SnO 2 (which is a phase detected in our samples via X-ray photoelectron spectroscopy (XPS); Supplementary Fig.…”
Section: Resultssupporting
confidence: 75%
“…Regarding the thermodynamics of adsorption on the surface, we have calculated an adsorption energy of 0.7 eV. The Sn–O bond length is found to be 2.31 Å, which is close to the experimental Sn–O bond length in SnO 2 (~2.1 Å 70 ). We also found that the O–O distance is stretched by over 0.1 Å beyond the bond length of the O 2 molecule; this elongation suggests that the O 2 molecule is likely to be dissociated on the surface and may subsequently participate in the formation of SnO 2 (which is a phase detected in our samples via X-ray photoelectron spectroscopy (XPS); Supplementary Fig.…”
Section: Resultssupporting
confidence: 75%
“…Here, CrO 2−x F x , which has a rutile (tetragonal) structure with the P4 2 /mnm space group, exhibits ferromagnetic behavior above room temperature and is regarded as a promising spintronic material because of its nearly 100% spin polarization at the Fermi level. 3,[29][30][31][32] To the best of our knowledge, the electrochemical properties of CrO 2−x F x including CrF 2 have never been reported, except for amorphous CrO 2−x compounds with 0 ≤ x ≤ 0.5. 33 Here, the CrO 2−x F x samples demonstrated a Q recha of 100-400 mA h g −1 at 298 K and a Q recha of 600-700 mA h g −1 at 318 K. The structural, magnetic, and electrochemical properties as a function of x in CrO 2−x F x are discussed in detail.…”
Section: Introductionmentioning
confidence: 98%
“…Transition-metal dioxides (TMO 2 ) with TM 4þ ions have attracted wide attention in the fields of materials science, condensed-matter physics, and geoscience due to their special high-pressure behavior. [7][8][9][10][11][12][13][14] For instance, CrO 2 , one of the prototypical half-metallic ferromagnets with T c ¼ 392-396 K, undergoes structural transitions under pressure, [15,16] and T c can be modified by pressure. [17] Firstprinciples calculations have shown that a transition from the ferromagnetic to the nonmagnetic state manifests in CrO 2 at the pyrite-Pnma transition.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Firstprinciples calculations have shown that a transition from the ferromagnetic to the nonmagnetic state manifests in CrO 2 at the pyrite-Pnma transition. [9] TiO 2 , widely applied in electrochemical solar cells due to its wide bandgap (3.1 eV), [18,19] may have potential application in industry as its bandgap can be modified by pressure. [10][11][12]14] Even more interestingly, the complicated Mott-like metal-insulator transition in VO 2 is attributed to the pressure-induced structural and electronic transitions, making VO 2 a promising phase-change material.…”
Section: Introductionmentioning
confidence: 99%